2020
DOI: 10.4000/activites.5517
|View full text |Cite
|
Sign up to set email alerts
|

Activity analysis in sports situations by articulating heterogeneous data: reflections and perspectives for design engineering

Abstract: This article examines the expansion of methodologies for articulating heterogeneous (experiential and behavioral) data within the course-of-action research program (Theureau, 2004, 2006, 2009, 2015). In the area of sports expertise, recent studies have articulated verbalizations based on conscious awareness and behavioral data from largely unconscious processes in order to shed light on expert instrumented activity. The methodological differences between these studies are highlighted, especially regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(44 reference statements)
0
3
0
1
Order By: Relevance
“…24 L'analyse de la littérature ouvre à plusieurs perspectives de recherches prometteuses. Premièrement, le développement de l'articulation de données hétérogènes (Adé, Gal-Petitfaux, Rochat, Seifert & Vors, 2020) pourra certainement permettre de gagner en complexité dans l'étude des émotions, en documentant simultanément différentes facettes des émotions dans l'activité des élèves.…”
Section: Discussionunclassified
“…24 L'analyse de la littérature ouvre à plusieurs perspectives de recherches prometteuses. Premièrement, le développement de l'articulation de données hétérogènes (Adé, Gal-Petitfaux, Rochat, Seifert & Vors, 2020) pourra certainement permettre de gagner en complexité dans l'étude des émotions, en documentant simultanément différentes facettes des émotions dans l'activité des élèves.…”
Section: Discussionunclassified
“…Hybrid methodologies have grown exponentially in recent years. Many terms are used: integrative research, mixed model (Johnson and Onwuegbuzie 2004), triangulation (Morse 1991), combined approach (Depraz and Desmidt 2019), multimethod (Greene 2015), articulating heterogeneous data (Adé et al 2020), mixed methods research, mixed methods, (Anadón 2019;Camerino, Castañer, and Anguera 2014;Creamer and Reeping 2020;Creswell and Plano Clark 2018;Hesse-Biber and Johnson 2015;Pluye et al 2018;Schweizer, del Rio Carral, and Santiago-Delefosse 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative or quantitative data may have a subordinate or equal relationship. For example, in sport, the study by Adé et al (2020), based on the cross-referencing of three studies, showed different types of articulation between the data, with a prevalence of qualitative data of lived experience over biomechanical data in a technological training device for swimming, or an equal relationship between quantitative and qualitative data on the use of different ice axes in glacier climbing. Other studies grant a predominance of quantitative kinetic data over qualitative data to study interpersonal coordination in rowing performance (Seifert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation